2020
DOI: 10.3390/cancers12113221
|View full text |Cite
|
Sign up to set email alerts
|

Marked Increased Production of Acute Phase Reactants by Skeletal Muscle during Cancer Cachexia

Abstract: Loss of skeletal muscle mass in cancer cachexia is recognized as a predictor of mortality. This study aimed to characterize the changes in the muscle secretome associated with cancer cachexia to gain a better understanding of the mechanisms involved and to identify secreted proteins which may reflect this wasting process. The changes in the muscle proteome of the C26 model were investigated by label-free proteomic analysis followed by a bioinformatic analysis in order to identify potentially secreted proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Although sarcopenia is well-known to be associated with worse treatment response in terms of reduced OS and RFS in GC [ 13 ], its impact on histologic response has not yet been elucidated. It can be argued that muscle mass may be involved in the drug pharmacokinetics and the synthesis of several acute-phase proteins [ 38 ] needed for the treatment response, but these results need to be confirmed due to the small sample size. Moreover, a greater pathological response may correspond to a reduction in dysphagia, and consequently, a better nutritional intake.…”
Section: Discussionmentioning
confidence: 99%
“…Although sarcopenia is well-known to be associated with worse treatment response in terms of reduced OS and RFS in GC [ 13 ], its impact on histologic response has not yet been elucidated. It can be argued that muscle mass may be involved in the drug pharmacokinetics and the synthesis of several acute-phase proteins [ 38 ] needed for the treatment response, but these results need to be confirmed due to the small sample size. Moreover, a greater pathological response may correspond to a reduction in dysphagia, and consequently, a better nutritional intake.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that muscle APR production, which requires mobilization of amino acids coming from muscle proteolysis, was associated with muscle atrophy in cachexia preclinical models, and it was negatively correlated with muscularity in cachectic cancer patients. 29 Therefore, by decreasing APR synthesis, AdipoRon could indirectly protect against protein catabolism. Finally, AdipoRon hindered muscular gene expression of components of the non‐canonical NF‐κB pathway that is involved in atrogene induction during cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…The collagen β(1-O)galactosyltransferase type 1 ( COLGALT1 ) has been identified, whose loss of function also causes muscle atrophy [ 46 ]. Many proteins such as RPL7A have increased expression in cancer [ 47 ]. Other critical regulators of muscle atrophy such as protein arginine methyltransferases ( PRMTs ) - PRTM5 is linked by the GCN method [ 48 ].…”
Section: Discussionmentioning
confidence: 99%